Novel evaluation of the expression patterns CD44 and MMP9 proteins in intracranial meningiomas and their relationship to the overall survival - Ahmed Abd Esattar Abd Elhakeem; Abdelhakeem A. Essa; Radwa Kamel Soliman; Ali Rabee Kamel Hamdan (Egyptian Journal of Neurosurgery, 2022)
Abstract Background Meningiomas are common primary brain neoplasms. CD44 is a cell surface glycoprotein receptor that is involved in matrix-mediated cell signaling and cell–matrix adhesion. Matrix metalloproteinase-9 (MMP-9) plays important role in angiogenesis and tumor invasion. The expression of CD44 protein membranous and cytoplasmic (CD44M and CD44C) has been reported in several tumors (such as lobular carcinoma, renal cell carcinoma, sinonasal melanoma, and lymphoma) except CNS tumors. Methods This study addressed the expression of CD44M and CD44C and MMP9 proteins in intracranial meningiomas and their relationship to overall survival. The expression patterns of CD44M&C and MMP-9 proteins were examined in 32 cases of benign meningiomas, 12 cases of atypical meningiomas, and 6 cases of anaplastic meningiomas using immunohistochemical staining methods. Results There was more evidence of CD44M expression in atypical and anaplastic meningioma (p =  < 0.001). Interestingly, Spearman correlation analyses revealed significant positive correlation between CD44M and MMP9 protein (r = 0.572, p =  < 0.001) in spite of the negative correlation between MMP9 and CD44 score (r = − 0.035 p = 0.405). There was a significant association between Ki67 protein expression and the grade of meningiomas (p < 0.001) and gender (p = 0.026). There was a significant correlation between overall survival (OS) and age, gender, tumor grade, and Ki-67. Conclusions Extensive CD44M expression in high-grade meningioma may reflect a tendency toward more invasive power of meningioma cells into surrounding structures (dura, bone, and brain).CD44M/MMP-9 axis presented by this study is open for future investigations.